The Simulation Analysis of Cutting Characteristics and Chip Formation Mechanism in Gear Skiving - Run Mao; Pei Tang; Yudong Zhang; Le Wang; Zheng Guo; Shimin Mao (Applied Sciences)
Gear skiving is an efficient and high-precision gear processing method, particularly advantageous for internal gears and coupling gears. However, the main limitation of its application is the rapid wear of skiving tools. This paper combines simulation analysis and numerical calculations to reveal the essential characteristics of the gear skiving process and the fundamental causes of tool wear. Firstly, it researches the distribution of cutting loads on the tool edges through the kinematic simulation analysis of gear skiving. Then, it analyzes the changing rule of working angle, clearance angle, tool inclination, and cutting speed and reveals the cutting state and chip flow patterns during the skiving process through numerical simulation calculations of gear skiving. Finally, it investigates the chip formation mechanism and the stress variation rule on the tool edges through finite element simulation of gear skiving. These analyses and calculations provide optimization guidance and methods for improving the cutting performance and the service life of skiving tools.